Mixed convective flow of MHD tangent hyperbolic nanofluid over a radiative stretching sheet in porous media with chemical reaction - Zubair, Muhammad; Khan, Husna A.; Khan, Nargis; Hashmi, Muhammad Sadiq; Salleh, Zabidin; Rezapour, Shahram; İnç, Mustafa (Sage Publications Ltd, 2025)
This work explores the mixed convective tangent hyperbolic nanofluid flow with magnetic field via radiative stretching sheet in a porous medium. While the flow problem is employed for non-Newtonian features, the Buongiorno nanofluid model is utilized for nanometer aspects that is, thermophoresis and Brownian motion. This model takes factors such as the heat source, chemical reaction effects, thermal conductivity, and for the porous medium uses Darcy-Forchheimer model. The nonlinear conservation equations of the partial differential are converted into nonlinear ordinary differential equations by appropriate transformations. To solve the evolving ordinary differential boundary value problem with suitable wall and free stream, an innovative numerical technique (Shooting Method) is applied. A rigorous parametric analysis is carried out to examine how various parameters affect the profiles of temperature, concentration, and velocity. Moreover, tables show the Sherwood and Nusselt numbers. More buoyancy ratio parameter causes the flow to slow, whereas improved mixed convection parameter raises the flow. The concentration profile falls as the Lewis number and chemical reaction parameter increase. The radiative parameter drastically raises temperatures. Concentration values decrease as the Brownian motion parameter increases. The study identifies uses for nanoparticles with specific properties in thermomagnetic processes.
Keywords: Darcy-Forchheimer flow; tangent hyperbolic nanofluid; heat generation; mixed convection; radiation; stretching sheet